Determinants of Capital Structure: A Cross-Country Comparison - Martin, James (2013)
This paper is a cross-country comparison of capital structure; specifically its firm level determinants and how these fluctuate between both Japan and the United States to test the efficacy of competing capital structure theories within contrasting institutional traditions. The purpose of the study is to bring to light the possible effect of such institutional differences on the capital structure decision for financial managers. I utilize a pre-crisis sample of 292 firms, 147 from Japan and 145 from the United States across a period of 1994-2007. Using panel data and a Blundell-Bond system-gmm procedure, the paper finds significant evidence for institutional impacts upon the debt-equity decision between the two countries, as well as significant evidence pertaining to the determinants in the two countries. I find the pecking order theory sound to describe the significant relationships in the United States, whilst in Japan there is evidence to support a confluence of hierarchal, trade-off and agency considerations.